2017
DOI: 10.1007/s11829-017-9522-8
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of amino acids and phenolic compounds in biochemical plant responses to feeding of two different herbivorous arthropod pests

Abstract: The study aimed at comparing the changes in the content of free amino acids, phenolic compounds and the activity of PAL and TAL caused by two piercingsucking arthropods: the grape mealybug (Pseudococcus maritimus Ehrh.) and the two-spotted spider mite (Tetranychus urticae Koch) in the leaves of orchid and strawberry, respectively. The obtained results show that the amino acid content and the ratio of amino acids to phenolic compounds increased in both plant species infested by the mealybug and the mite. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Significantly enhanced production of phytoalexins was also observed in response to the elicitation of signalling molecules such as SA, methyl jasmonate and methyl-β-cyclodextrins in plants [ 10 ]. The induction of phytoalexin biosynthesis was demonstrated in many plant species in response to insects [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Dual-choice tests involving varied phytoalexin contents carried out by Hart [ 21 ] revealed that an isoflavonoid phytoalexin(s) had feeding-deterrent properties towards insects.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly enhanced production of phytoalexins was also observed in response to the elicitation of signalling molecules such as SA, methyl jasmonate and methyl-β-cyclodextrins in plants [ 10 ]. The induction of phytoalexin biosynthesis was demonstrated in many plant species in response to insects [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Dual-choice tests involving varied phytoalexin contents carried out by Hart [ 21 ] revealed that an isoflavonoid phytoalexin(s) had feeding-deterrent properties towards insects.…”
Section: Introductionmentioning
confidence: 99%
“…The TFA also played a significant role in BPH infestation on rice where most of the resistant landraces, including Ptb33 registered lower TFA content. This might be attributable that resistant cultivars against sap suckers usually possess a lower quantity of TFA by limiting the nutritive value of plant tissues for the herbivores Golan et al (2017). Biplot of PCA suggests that TFA, RS and N content were in a close association in the healthy rice plants, while the distance between the former and two later was largest after BPH feeding.…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence that the amount of amino acid and soluble nitrogen in plants are important in determining the growth and reproduction of sap sucking insects (Mengel & Kirkby, 1982;Jansson & Smilowitz, 1986;Cole, 1997;Altieri & Nicolls, 2003;Chau et al, 2005;Golan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies that indicate changes in the amount of N and K in plants can affect the population ecology of aphids and other sap-feeding insects (van Emden, 1966;Perrenoud, 1990;Waring & Cobb, 1992;Cisneros & Godfrey, 2001;Awmack & Leather, 2002;Boyer et al, 2003;Gratton & Denno, 2003;Golan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation